The power of culture driving today's organisation - Barker, Carolyn; Coy, Robyn (Management today series, 2004)
Helps managers with the means to harness the power of culture to drive strategy. This book explains the concept of organisational culture, its management and leadership implications, and its application. It explores the skills managers need to assess, comprehend, integrate and manage culture - how to turn the soft, people stuff into an advantage.